Low Temperature Aluminothermic Reduction of Natural Sepiolite to High-Performance Si Nanofibers for Li-Ion Batteries - Zhao, Mingyuan; Yang, Shaobin; Dong, Wei (Frontiers in Chemistry, 2022)
Nanostructure silicon is one of the most promising anode materials for the next-generation lithium-ion battery, but the complicated synthesis process and high cost limit its large-scale commercial application. Herein, a simple and low-cost method was proposed to prepare silicon nanofibers (SNF) using natural sepiolite as a template via a low-temperature aluminum reduction process. The low temperature of 260°C during the reduction process not only reduced the production cost but also avoided the destruction of the natural sepiolite structure caused by the high temperature above 600°C in the traditional magnesium thermal reduction process, leading to a more complete nanofiber structure in the final product. For the first time, the important role of Mg-O octahedral structure in the maintenance of nanofiber structure during the process of low-temperature aluminothermic reduction was verified by experiments. When used as an anode for lithium-ion batteries, SNF yield a high reversible capacity of 2005.4 mAh g−1 at 0.5 A g−1 after 50 cycles and 1017.6 mAh g−1 at 2 A g−1 after 200 cycles, remarkably outperforming commercial Si material. With a low-cost precursor and facile approach, this work provides a new strategy for the synthesis of a commercial high-capacity Si anode.